Plant Protein Proteinase Inhibitors: Structure and Mechanism of Inhibition - S. Bateman, Katherine; N.G. James, Michael (Current Protein and Peptide Science, 2011)
This review outlines known examples of the three-dimensional structures of protein proteinase inhibitors from plants. Three families of enzymes, serine proteinases, carboxypeptidases and cysteine proteinases, are targeted by at least a dozen inhibitor families, with the majority of them adopting the standard mechanism of inhibition towards the serine proteinases. All of the inhibitors discussed maintain compact and stable inhibitory domains that bind to the active site of their target proteinases and prevent access to the substrate molecules. One interesting highlight is the knottin group. Three separate inhibitor families utilize the overall knottin fold in a different way. This fold can accommodate extensive sequence variation and for each of the squash, Mirabilis and Potato carboxypeptidase families, the proteinase-binding residues are found at a different location. Plants have also evolved additional strategies to regulate proteinase activity, such as linking inhibitory domains and targeting multiple enzymes at once. The structural aspects of these strategies are discussed in the review.
Keywords: Inhibition mechanism